2021
DOI: 10.3390/ijerph18031194
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Perfluoroalkyl Substances with Prevalence of Metabolic Syndrome in Highly Exposed Young Adult Community Residents—A Cross-Sectional Study in Veneto Region, Italy

Abstract: Background: Studies on the association between perfluoroalkyl substances (PFAS) and metabolic syndrome (MetS) are limited, and results are inconsistent. We aimed to examine the associations between PFAS serum levels and the prevalence of MetS among highly exposed young adults (ages 20–39) residents of a large area of the Veneto Region (North-Eastern Italy) primarily stemming from PFAS water contamination before September 2013. A total of 15,876 eligible young adult residents living in the investigated municipa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 45 publications
4
19
0
Order By: Relevance
“…The relationship between PFAS and HDL-c is also unclear. In a previous study from the US [ 29 ], PFOA was associated with HDL-c positively, as with the current results, while negatively based on another study from Italy [ 30 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The relationship between PFAS and HDL-c is also unclear. In a previous study from the US [ 29 ], PFOA was associated with HDL-c positively, as with the current results, while negatively based on another study from Italy [ 30 ].…”
Section: Discussionsupporting
confidence: 89%
“…In 3629 American adults aged ≥20 years, there were inverse associations between triglycerides and PFNA and PFDA (respectively, 1.00 and 0.25) [ 31 ]. In a previous study from Italy, including 15,876 young adults aged 20–39 years, PFNA (0.53–0.58) was negatively associated with BMI [ 30 ]. Although the mechanisms by which PFAS may decrease the odds of certain biomarkers are unknown, the inverse association observed in this study may contemplate the anti-inflammatory and/or reduced insulin resistance effects of certain PFAS, as well as their potentially high oxygen-carrying capacity [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results did not support the hypothesis of an association between PFAS and metabolic syndrome. However, a statistically significant positive association between PFAS plasma concentration and individual components of the metabolic syndrome, namely increased blood pressure and elevated plasma triglycerides, was observed (44).…”
Section: Pfas-related Metabolic and Hypertensive Disordersmentioning
confidence: 90%
“…A large population-based cross-sectional observational study performed in the Veneto region found an association between some PFAS (in particular PFOA, PFOS, and PFHxS) and total, HDL and LDL cholesterol, as well as between PFOA,PFHxS and triglycerides (43,44).…”
Section: Pfas-related Metabolic and Hypertensive Disordersmentioning
confidence: 99%
“…[47][48][49] Three studies have reported negative associations between PFAS body burden and body size characteristics. 47,50,51 Moreover, several studies have reported no associations between PFAS body burden and body size. [52][53][54][55][56] To date, epidemiological studies do not support consistent associations between PFAS and obesity.…”
Section: Obesitymentioning
confidence: 99%